The Methodology of Fatwa Issuance and the Impact of the School of Thought (Madhhab) on Fatwas by the North Sumatra MUI - Rahmadi, Fuji; Firmansyah, Heri (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
Shafi'i madhhab followers constitute a majority among Muslims in North Sumatra. This article aims to explore the fatwa methodology and the impact of madhhab influences on decisions issued by the North Sumatra MUI. The research seeks to identify which Sunni schools of thought guide the MUI's fatwa decisions. This paper addresses two main issues: the methodology employed by the North Sumatra MUI in issuing fatwas, and the influence of madhhab thinking on fatwas, particularly those related to prayers issued between 2000 and 2010. To analyze the fatwa methodology of the North Sumatra MUI, this article employs three theories of legal interpretation: bayÄni, ta'lÄ«lÄ« and istislÄhÄ«. The approach taken in this paper invoÃ£Ã£lves content analysis, specifically examining fatwa texts to address the research focus. This study centers on referencing Madhhab perspectives found in the official fatwa decisions of the North Sumatra MUI. This study is crucial to assess the extent of Madhhab influence on issued fatwas, particularly within the regional context at the provincial level. Methodologically, the study found that the North Sumatra MUI employs three approaches in its fatwa process: bayÄni, ta'lÄ«lÄ« and istislÄhÄ«. Regarding the influence of Madhhab thinking, the study discovered that the North Sumatra MUI referenced the viewpoints of the four Madhhabs' imams in the three fatwas analyzed. Based on this research, it is evident that the fatwas draw from not only the Shafi'i school but also from the other three schools. Among the fatwas analyzed, the Hanafi school predominates, appearing in all three cases, with the Shafi'i school appearing twice, and the Maliki and Hanbali schools each appearing once.